Diagnostic utility of SOX11 immunohistochemistry in differentiating cutaneous spread of mantle cell lymphoma from primary cutaneous B‐cell lymphomas. (10th February 2016) - Hsi, Andy C.; Hurley, M. Yadira; Lee, Sena J.; Rosman, Ilana S.; Pang, Xiaofan; Gru, Alejandro; Schaffer, András
Abstract : Background: Mantle cell lymphoma (MCL) is associated with the worst prognosis among low‐grade B‐cell lymphomas. While cutaneous involvement by nodal or systemic MCL is uncommon, its differentiation from primary cutaneous B‐cell lymphoma (CBCL) or cutaneous involvement by other extra‐cutaneous BCL is challenging as neither histomorphology nor immunophenotype can be absolutely specific. We analyzed the diagnostic utility of SOX11 immunohistochemistry in differentiating secondary cutaneous MCL from other low‐grade CBCL. Methods: Immunohistochemical staining with anti‐SOX11 antibody was performed on 8 cases of secondary cutaneous MCL, 16 secondary cutaneous CLL, 20 primary cutaneous MZL, 12 cutaneous FCL (6 primary, 6 secondary), 7 primary cutaneous DLBCL, leg type, 5 systemic DLBCL and 3 B‐ALL. SOX11 and cyclin D1 staining were compared in secondary cutaneous MCL. Results: Nuclear SOX11 staining was seen in seven of eight cases (88%) of secondary cutaneous MCL, including a case with minimal cyclin D1 expression. All other CBCL lacked detectable nuclear SOX11 expression. The sensitivity and specificity for SOX11 in MCL were 87.5 and 100%, respectively. Both the sensitivity and specificity for combined SOX11 and cyclin D1 immunohistochemistry were 100%. Conclusion: SOX11 immunohistochemistry could be a useful adjunct in distinguishing secondary cutaneous MCL from other CBCL.